2000
DOI: 10.1093/ps/79.9.1264
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effects of various lipopeptides and interferon-γ on the humoral immune response of chickens

Abstract: The adjuvant effects of various lipopeptides and recombinant chicken interferon gamma (IFN-gamma) on the humoral immune response of laying hens was investigated in four immunization studies. We used the lipopeptide Pam3Cys-Ser-(Lys)4 (PCSL), the conjugate P-Th1 consisting of the lipopeptide P3CS and the T-helper epitope Th1 (FISEAIIHVLHSRHPG), and the conjugate P-Th2 of the lipopeptide P3CSS and the T-helper epitope Th2, which corresponds to the peptide EWEFVNTPPLV, as adjuvants. Human serum albumin (HSA), rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…It was also shown that IgY was relatively stable under different conditions, including heat, pressure, alkalinity, acidity (> pH 3.5), and in the presence of proteolytic enzymes, such as trypsin and chymotrypsin (Shimizu et al, 1992). Therefore, the ability to produce high amounts of antigen-specific IgY with reasonably high stability makes production of IgY against various viral antigens a viable option to be used in diagnostics (Erhard et al, 2000), antibiotic-alternative therapy (Carlander et al, 2000), and therapeutics (Schade et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that IgY was relatively stable under different conditions, including heat, pressure, alkalinity, acidity (> pH 3.5), and in the presence of proteolytic enzymes, such as trypsin and chymotrypsin (Shimizu et al, 1992). Therefore, the ability to produce high amounts of antigen-specific IgY with reasonably high stability makes production of IgY against various viral antigens a viable option to be used in diagnostics (Erhard et al, 2000), antibiotic-alternative therapy (Carlander et al, 2000), and therapeutics (Schade et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that compounds with different degree of acylation may bind different receptor complexes and this may result in different gene activation [13]. Triacetylated lipopeptide has been shown to act as an adjuvant, initiating a specific immune response in chickens resulting in increased antibody titres against the immunising antigens [21]. Zebrafish and pufferfish TLR1 equivalents have been reported [14e16] and are expressed at low levels in zebrafish muscle and heart.…”
Section: Toll-like Receptormentioning
confidence: 99%
“…together with IFN-g and a synthetic lipopeptide but not with cytokine alone. (149) Antibody and T cell proliferative responses to immunization with MDV glycoprotein B were strongly enhanced when latex microspheres coated with rIL-2 were coinjected with antigen into 3-week-old chickens. (150) Few studies have assessed the immunomodulatory activity of plasmid-expressed cytokines.…”
Section: Cytokines As Vaccine Adjuvantsmentioning
confidence: 99%